CONSORT Statement for randomized trials of nonpharmacologic treatments: a 2017 update and a CONSORT extension for nonpharmacologic trial abstracts - Boutron, I; Altman, D; Moher, D; Schulz, K; Ravaud, P; CONSORT NPT group (American College of Physicians, 2017)
Incomplete and inadequate reporting is an avoidable waste that reduces the usefulness of research. The Consolidated Standards of Reporting Trials (CONSORT) Statement is an evidence-based reporting guideline that aims to improve research transparency and reduce waste. In 2008, the CONSORT group developed an extension to the original statement that addressed methodologic issues specific to trials of nonpharmacologic treatments (NPTs) such as surgery, rehabilitation or psychotherapy. This article describes an update of that extension and presents a CONSORT extension for reporting abstracts of NPT trials. To develop these materials, we reviewed pertinent literature published up to July 2016, surveyed authors of NPT trials, and conducted a consensus meeting with editors, trialists and methodologists. Changes to the CONSORT Statement extension for NPT trials include wording modifications to improve readers’ understanding and the addition of 3 new items. New items address whether and how adherence of participants to interventions was assessed or enhanced, the description of any attempts to limit bias if blinding was not possible, and specification of the delay between randomization and the initiation of the intervention. The CONSORT extension for abstracts of NPT trials includes 2 new items that are not specified in the original CONSORT Statement for abstracts. The first addresses the reporting of eligibility criteria for centers where the intervention is performed and for care providers. The second addresses reporting of any important changes to the intervention from what was planned. Both the updated CONSORT extension for NPT trials and CONSORT extension for NPT trial abstracts should help authors, editors, and peer reviewers improve the transparency of NPT trial reports.